1994
DOI: 10.1079/bjn19940058
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of medium chain fatty acids: in vivo studies in pigs devoid of exocrine pancreatic secretion

Abstract: In order to study the influence of pancreatic enzyme secretion on the intestinal absorption of mediumchain fatty acids (MCFA), three growing pigs (mean body-weight 61 kg) with ligated and severed pancreatic ducts were fitted with a permanent fistula in the duodenum and with two catheters in the portal vein and carotid artery respectively. An electromagnetic flow probe was also set up around the portal vein. A mixture of octanoic and decanoic acids, esterified as medium-chain triacylglycerols, together with mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…Several authors found relatively constant blood flow values after ingestion of the meal (Guillot et al, 1993;Guillot et al, 1994;Lang et al, 1999). One can easily assume that portal blood flow variations in the present work were similar for all the animals and that they consequently interfered in the same way for all the three diets.…”
Section: Portal Absorption Calculationssupporting
confidence: 62%
See 1 more Smart Citation
“…Several authors found relatively constant blood flow values after ingestion of the meal (Guillot et al, 1993;Guillot et al, 1994;Lang et al, 1999). One can easily assume that portal blood flow variations in the present work were similar for all the animals and that they consequently interfered in the same way for all the three diets.…”
Section: Portal Absorption Calculationssupporting
confidence: 62%
“…14 C meal absorption rate was calculated as: "portal absorption of 14 C / 14 C content in the meal". Blood flow per min and per kg body weight could be estimated thanks many references using growing pigs (Rérat et al, 1987;Simoes Nunes et al, 1989;Rérat et al, 1991;Rérat et al, 1992;Guillot et al, 1993;Guillot et al, 1994;Rérat et al, 1996;Santamaria et al, 1997;Lang et al, 1999;Le Floc'h et al, 1999;Vaugelade et al, 2000).…”
Section: Portal Absorption Calculationsmentioning
confidence: 99%
“…In fact, it is known that meal ingestion is followed by a small rise in portal blood flow during the first 1-2 postprandial hours and individual variations in pig portal blood flow have been established at between 2.8 and 5.7% [20]. Several authors found relatively constant blood flow values after ingestion of the meal [5,6]. One can easily assume that portal blood flow variations in the present work were similar for all the animals.…”
Section: Portal Absorption Calculationssupporting
confidence: 59%
“…Thus the most interesting features concern the influence of absorption kinetics on the ability of organs such as the liver or the peripheral tissues to store and release nutrients and the utilisation of dynamic aspects in the analysis of the role played by the "time" factor in protein tissue metabolism. This methodology enabled to study the digestion of some carbohydrates [167], proteins [175] and medium-chain triglycerides [73,74] in relation with hepatic metabolism and with peripheral tissue metabolism, according to their technological pretreatment (enzyme prehydrolysis...).…”
Section: Hepatic Handling Of Absorbed Nutrientsmentioning
confidence: 99%